Bioinformatic Analyzes of the Association Between Upregulated Expression of JUN Gene via APOBEC-Induced FLG Gene Mutation and Prognosis of Cervical Cancer - Chen, Huan; Zhao, Liyun; Liu, Jiaqiang; Zhou, Housheng; Wang, Xi; Fang, Xiaoling; Xia, Xiaomeng (Frontiers in Medicine, 2022)
Globally, cervical cancer is the most common malignant tumor of female reproductive system and its incidence is only second after breast cancer. Although screening and advanced treatment strategies have improved rates of survival, some patients with cervical cancer still die due to metastasis and drug resistance. It is considered that cancer is driven by somatic mutations including single nucleotide, small insertions/deletions, copy number, and structural variations, as well as epigenetic changes. Previous studies have shown that cervical intraepithelial neoplasia is associated with copy number variants and/or mutations in cancer-related genes. Further, cervical cancer is also related to genetic mutations. The present study analyzed the data on somatic mutations of cervical squamous cell carcinoma in the Cancer Genome Atlas database. It was evident that APOBEC-related mutation of FLG gene can upregulate expression of JUN gene and ultimately lead to poor prognosis for cervical cancer patients. Therefore, the findings of the current study provide a new direction for future treatment of cervical cancer.